Mitigating Uncertainty in Mining Infrastructure Development: A Case of Zimbabwe`s Extractive Industry Legal Risk - Gerber, Leonardus J. (University of Pretoria, 2021)
Mini Dissertation (LLM)--University of Pretoria, 2019.